Perbandingan Rasio Keuangan (Likuiditas, Leverage, Profitabilitas dan Aktivitas) pada PT Gudang Garam Tbk dan PT HM Sampoerna Tbk Tahun 2021 - Atti Rasnawati; Nadiatul khoiroh; Fauziah Fauziah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study compares the financial ratios between PT Gudang Garam Tbk and PT HM Sampoena in 2021 which aims to see the capabilities of the two companies in each of their financial ratios. The results of this study indicate that the ability of the two companies, namely PT Gudang Garam Tbk and PT HM Sampoerna Tbk, in financial performance with four ratios, namely: the liquidity ratio with the proxy current ratio that PT Gudang Garam Tbk is in better condition than PT HM Sampoerna Tbk and the quick ratio of the two companies is not in good condition, the cash ratio of PT HM Sampoerna Tbk is in good condition than PT Gudang Garam Tbk. The leverage ratio proxied by the debt to asset ratio and the debt to equity ratio of the two companies shows a healthy condition. Meanwhile, the activity ratio, including fixed asset turnover, PT HM Sampoerna Tbk generates more income, as well as its total asset turnover is more than that of PT Gudang Garam Tbk. The profitability ratio proxied by net profit margin (NPM), return on assets (ROA) and return on equity (ROE) at PT HM Sampoerna Tbk is higher in value than PT Gudang Garam Tbk.